Linkages to Budgetary Control and Budgetary Absorption Performance - Gunawan, Arwan; Yadiati, Winwin; Suharman, Harry; Sofia, K. Poppy (International Journal of Economics and Financial Issues, 2020)
This Study aims to examine the effect of budgetary control on the performance of budgetary absorption. The Research method used was a survey of a population comprising 548 provincial/Regency/city governments in Indonesia with 231 samples. Primary data consisting of 33 samples were collected using questionnaires, and analysed quantitayively testing method used Partial Least Square-Path Modeling ( PLS-PM), whereas data processing methods used smartpls. The Research method used was a survey of a population comprising 548 provincial/Regency/city governments in Indonesia with 231 samples. Primary data consisting of 33 samples were collected using questionnaires, and analysed quantitayively testing method used Partial Least Square- Path Modeling (PLS-PM), whereas data processing methods used smartpls. The results of the study indicate that budgetary control has a significant positive effect on the performance of budgetary absorption. Thus, budgetary control can be said to have a high thrust to increase the performance of budgetary absorption. This contributes to the acceleration of economic development of regional governments in a country. Keywords: Budgetary Control, Budgetary Absorption Performance, Local Government JEL Classifications: H61, H72 DOI: https://doi.org/10.32479/ijefi.10515